Analysis of the radio network algorithm scheduling on the basis of LTE technology - Токарь, Л.А. (Radiotekhnika, 2012)
The basic advantages of the mobile SHPD distribution in transition to the LTE next generation technology are shown. The problems of design and analysis of the LTE radio network scheduling algorithm are considered.